Integrative Transcriptome Sequencing Reveals the Molecular Difference of Maturation Process of Ovary and Testis in Mud Crab Scylla paramamosain - Cui, Wenxiao; Yang, Qin; Zhang, Yin; Farhadi, Ardavan; Fang, Huan; Zheng, Huaiping; Li, Shengkang; Zhang, Yueling; Ikhwanuddin, Mhd; Ma, Hongyu (Frontiers in Marine Science, 2021)
The mud crab Scylla paramamosain is a species with significant sexual dimorphism in growth rate and body size, of which the females are of higher economic and nutritional values than the males. Accordingly, there is an urgent need to explore the molecular mechanism underlying sex determination and gonadal differentiation. The single-molecule long-read technology combining with RNA sequencing was employed to construct a full-length transcriptome for gonads of S. paramamosain. In total, 1,562,819 FLNC reads were obtained from 1,813,758 reads of insert (ROIs). Among them, the 10,739 fusion isoforms corresponded to 23,634 reads and were involved in 5,369 genes in the reference annotation. According to the criteria for new transcripts, a total of 213,809 isoforms were recognized as novel transcripts and then matched against GO, KEGG, NR, Swissprot, and KOG databases. We also identified 22,313 SSRs, 169,559 lncRNAs, and 25,451 SNPs. Additionally, 349,854 AS events from 8,430 gene models were detected and 5,129 polyadenylation sites were profiled from 3,090 genes. GO and KEGG annotation indicated that AS and APA probably play important roles in the gonadal development and maturation. Besides, the DEGs associated with gonadal development and maturation were identified and analyzed based on the RNA-Seq data.